Impact of Lateral Flow on Surface Water and Energy Budgets Over the Southern Great Plains—A Modeling Study. Issue 12 (15th June 2021) - Yang, Zhao; Huang, Maoyi; Berg, Larry K.; Qian, Yun; Gustafson, William I.; Fang, Yuanhao; Liu, Ying; Fast, Jerome D.; Sakaguchi, Koichi; Tai, Sheng‐Lun
Abstract: As the horizontal grid spacing decreases, treatment of hydrologic processes in land surface models (LSMs), such as the lateral flow of surface and subsurface flow, need to be explicitly represented. Unlike previous studies that mainly focused on the mountainous regions, in this study, the offline Weather Research and Forecasting (WRF)‐Hydro model is employed to study the impact of lateral flow on soil moisture and energy fluxes over the relatively flat southern Great Plains (SGP). The vast amount of measurements over the SGP provide a unique opportunity to assess the model behavior. In addition, newly developed land surface properties and input forcing are ingested into the model, in an attempt to reduce uncertainties associated with the initial and boundary forcing and help to identify model deficiencies. Our results show that the more realistic inputs (parameters, soil types, forcing) lead to larger underestimation of latent heat flux and dry bias, indicating the existence of model structural uncertainty (embedded errors) in WRF‐Hydro that need to be characterized to inform future model development efforts. Including lateral flow processes partly mitigates the model deficiencies in representing hydrologic processes and alleviates the dry bias. In particular, both surface and subsurface lateral flow increase soil moisture mainly over the lower elevations, except that subsurface flow also affects soil moisture over steeper terrains. Additional simulations are performed to assess the effect of routing resolution on model results. When LSM resolution is high, noticeable differences in soil moisture are produced between different routing resolutions especially over steep terrain. Whereas when LSM resolution is coarse, differences between routing resolutions become negligible, especially over flat terrain. Key Points: Default parameter values in Noah‐MP lead to underestimation of latent heat fluxes and overestimation of soil moisture The introduction of lateral flow via Weather Research and Forecasting‐Hydro can alleviate the biases in latent heat fluxes in high‐resolution simulations It is crucial to address parametric uncertainty in both land surface and routing schemes for realistic surface flux simulations